The Impact on Ovarian Reserve of Different Hemostasis Methods in Laparoscopic Cystectomy: A Systematic Review and Meta-analysis - Baracat, Clara Micalli Ferruzzi; Abdalla-Ribeiro, Helizabet Salomão Ayroza; Araujo, Raquel Silveira da Cunha; Bernando, Wanderley Marques; Ribeiro, Paulo Ayroza (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective The objective of this review was to analyze the impact on ovarian reserve of the different hemostatic methods used during laparoscopic cystectomy.Data Sources The studies were identified by searching electronic databases (MEDLINE, Embase, Cochrane, LILACS) and scanning reference lists of articles.Methods of Study Selection We selected clinical trials that assessed the influence of hemostatic techniques on ovarian reserve in patients with ovarian cysts with benign sonographic appearance submitted to laparoscopic cystectomy by stripping technique. The included trials compared different laparoscopic hemostatic techniques: suture, bipolar electrocoagulation, ultrasonic energy and hemostatic sealants. The outcomes evaluated were level of serum anti-Mullerian hormone (AMH) and antral follicle count (AFC). The possibility of publication bias was evaluated by funnel plots.Tabulation, Integration and Results Twelve trials involving 1,047 patients were evaluated. Laparoscopic suture was superior to bipolar coagulation when evaluating serum AMH and AFC, in the 1st, 3rd, 6th and 12th month after surgery. In the comparison between bipolar and hemostatic sealants, the results favored the use of hemostatic agents. The use of ultrasonic energy was not superior to the use of bipolar energy.Conclusion We recommend suture for hemostasis during laparoscopic cystectomy.
Keywords: laparoscopy; ovarian reserve; ovarian cyst; systematic review; meta-analysis